Early Palliative Care Consultation in the Medical ICU: A Cluster Randomized Crossover Trial. Issue 12 (December 2019) - Ma, Jessica; Chi, Stephen; Buettner, Benjamin; Pollard, Katherine; Muir, Monica; Kolekar, Charu; Al-Hammadi, Noor; Chen, Ling; Kollef, Marin; Dans, Maria
Abstract : Objectives: To assess the impact of early triggered palliative care consultation on the outcomes of high-risk ICU patients. Design: Single-center cluster randomized crossover trial. Setting: Two medical ICUs at Barnes Jewish Hospital. Patients: Patients ( n = 199) admitted to the medical ICUs from August 2017 to May 2018 with a positive palliative care screen indicating high risk for morbidity or mortality. Interventions: The medical ICUs were randomized to intervention or usual care followed by washout and crossover, with independent assignment of patients to each ICU at admission. Intervention arm patients received a palliative care consultation from an interprofessional team led by board-certified palliative care providers within 48 hours of ICU admission. Measurements and Main Results: Ninety-seven patients (48.7%) were assigned to the intervention and 102 (51.3%) to usual care. Transition to do-not-resuscitate/do-not-intubate occurred earlier and significantly more often in the intervention group than the control group (50.5% vs 23.4%; p < 0.0001). The intervention group had significantly more transfers to hospice care (18.6% vs 4.9%; p < 0.01) with fewer ventilator days (median 4 vs 6 d; p < 0.05), tracheostomies performed (1% vs 7.8%; p < 0.05), and postdischarge emergency department visits and/or readmissions (17.3% vs 38.9%; p < 0.01). Although total operating cost was not significantly different, medical ICU ( p < 0.01) and pharmacy ( p < 0.05) operating costs were significantly lower in the intervention group. There was no significant difference in ICU length of stay (median 5 vs 5.5 d), hospital length of stay (median 10 vs 11 d), in-hospital mortality (22.6% vs 29.4%), or 30-day mortality between groups (35.1% vs 36.3%) ( p > 0.05). Conclusions: Early triggered palliative care consultation was associated with greater transition to do-not-resuscitate/do-not-intubate and to hospice care, as well as decreased ICU and post-ICU healthcare resource utilization. Our study suggests that routine palliative care consultation may positively impact the care of high risk, critically ill patients. Abstract : Supplemental Digital Content is available in the text.